Cobalt/Peracetic Acid: Advanced Oxidation of Aromatic Organic Compounds by Acetylperoxyl Radicals - Kim, Juhee; Du, Penghui; Liu, Wen; Luo, Cong; Zhao, He; Huang, Ching-Hua (Environmental Science & Technology, 2020)
Peracetic acid (PAA) is increasingly used as an alternative disinfectant and its advanced oxidation processes (AOPs) could be useful for pollutant degradation. Co(II) or Co(III) can activate PAA to produce acetyloxyl (CH3C(O)O•) and acetylperoxyl (CH3C(O)OO•) radicals with little •OH radical formation, and Co(II)/Co(III) is cycled. For the first time, this study determined the reaction rates of PAA with Co(II) (kPAA,Co(II) = 1.70 × 101 to 6.67 × 102 M–1·s–1) and Co(III) (kPAA,Co(III) = 3.91 × 100 to 4.57 × 102 M–1·s–1) ions over the initial pH 3.0–8.2 and evaluated 30 different aromatic organic compounds for degradation by Co/PAA. In-depth investigation confirmed that CH3C(O)OO• is the key reactive species under Co/PAA for compound degradation. Assessing the structure–activity relationship between compounds’ molecular descriptors and pseudo-first-order degradation rate constants (k′PAA• in s–1) by Co/PAA showed the number of ring atoms, EHOMO, softness, and ionization potential to be the most influential, strongly suggesting the electron transfer mechanism from aromatic compounds to the acetylperoxyl radical. The radical production and compound degradation in Co/PAA are most efficient in the intermediate pH range and can be influenced by water matrix constituents of bicarbonate, phosphate, and humic acids. These results significantly improve the knowledge regarding the acetylperoxyl radical from PAA and will be useful for further development and applications of PAA-based AOPs.